Pengaruh Perkembangan Karir, Pendapatan dan Pengawasan Supervisor Terhadap Kepuasan Kerja Karyawan Magang Bakti: Studi Kasus BCA KCU Masjid Lama - Trevinata bella; Juhaini Alie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine whether career development, income, and supervisor supervision have an influence on job satisfaction of BCA KCU MASJID LAMA bakti intern employees. The population in the study were all apprentice employees of BCA KCU MASJID LAMA, totaling 100 people. The sample method used in this study is the saturated sample method because of sampling all employees. This study uses multiple linear regression analysis techniques. The results of this study indicate that career development and supervisor supervision have a significant effect on job satisfaction while income has no significant effect on job satisfaction.